Oral injuries as syphilis diagnosis: case report - Meireles, Luísa Souza; Coelho, Juliana Monteiro Ramos; Alvim, Marina Ramos; Silveira, Filomena Aste; Martins, Carolina de Freitas Narciso; Barros, Camila Fonseca; Galvão, Carolina; Godefroy, Philippe (Brazilian Journal of Sexually Transmitted Diseases, 2022)
Syphilis can present a variety of clinical manifestations as a consequence of the tropism that Treponema pallidum causes to various organs and body tissues. The oral cavity can be affected in all stages of the disease, therefore diagnosis requires knowledge of multidisciplinary health professionals. Even with the introduction of penicillin in the last century and initiatives of sexually transmitted diseases prevention, an increase in the incidence of syphilis has been observed, which indicates a public health issue. This paper presented the case of a patient with syphilitic chancre in the oral cavity, whose dental surgeon diagnosed an injury and referred her to the city sexually transmitted diseases ambulatory for treatment.